Peningkatan Hasil Belajar Keterampilan Menyimak Dongeng melalui Media Boneka Jari Siswa Kelas II MI An-Najihah Babussalam Madiun - Larassati, Larassati; Alifah, Pipiet (FONDATIA, 2025)
Listening skills constitute an essential component of Indonesian language learning, contributing to the development of students’ overall language competence. However, students' limited comprehension of fables delivered by teachers highlights the need for innovative instructional media. This issue often stems from the use of monotonous and insufficiently interactive methods, which diminish students’ interest and focus. This study aims to improve learning outcomes in listening to fables through the application of finger puppet media among second-grade students at MI An-Najihah Babussalam Kebonsari Madiun in the 2024–2025 academic year. The research employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The study involved 20 students. Data were collected through observation, tests, and documentation, and were analyzed both qualitatively and quantitatively. The findings show a significant improvement in both learning outcomes and student engagement. Mastery learning increased from 45% in the pre-cycle to 80% in Cycle I, and reached 95% in Cycle II. Learning activities also improved from 50% to 90%. These results indicate that finger puppet media are effective in enhancing listening skills for fables and in fostering a more engaging, active, and enjoyable learning environment. The implications of this study underscore the importance of incorporating visual-interactive media in the teaching of listening skills at the elementary school level.